Structure of the semigroup OT_n - Pekhterev, V. O. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We study the structure of the semigroup OT_n, which is a unique (up to an isomorphism) R-section of the semigroup T_n. For this semigroup, we describe Green relations, determine regular and nilpotent elements, describe maximal nilpotent subsemigroups, and determine the unique irreducible system of generatrices and maximal subsemigroups.